1987
DOI: 10.1002/clc.4960100613
|View full text |Cite
|
Sign up to set email alerts
|

Sinus arrest caused by atenolol‐verapamil combination

Abstract: Summary: A case on concomitant atenolol-verapamil therapy for hypertension and angina pectoris, developing sinus arrest and life-threatening bradycardia is described. The complication occurred with low doses of both the agents and normal electrophysiologic status of the heart. The example suggests that pharmacodynamic synergism contributes more than pharmacokinetic interaction in causing adverse reactions during beta blocker-verapamil therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Although placebo was ingested daily during the control phase, the slightly red color in urine during the rifampicin phase did not allow a true blinding of the phases. Previous studies have reported that the calcium channel antagonists verapamil and diltiazem can increase the arrhythmogenic potential of atenolol (Findlay et al 1984;Misra et al 1987;Sagie et al 1991). A pharmacodynamic mechanism can explain these interactions, because both the two calcium-channel antagonists and atenolol can cause bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Although placebo was ingested daily during the control phase, the slightly red color in urine during the rifampicin phase did not allow a true blinding of the phases. Previous studies have reported that the calcium channel antagonists verapamil and diltiazem can increase the arrhythmogenic potential of atenolol (Findlay et al 1984;Misra et al 1987;Sagie et al 1991). A pharmacodynamic mechanism can explain these interactions, because both the two calcium-channel antagonists and atenolol can cause bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Co‐administration of atenolol with verapamil and diltiazem can cause symptomatic bradycardia and sinus arrest (Findlay et al 1984; Misra et al 1987; Sagie et al 1991). This can be explained as a pharmacodynamic interaction, because both calciumchannel antagonists and atenolol have a negative chronotropic effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that the synergistic effects of β-adrenergic blockers and calcium channel blockers of the verapamil or diltiazem type on BP, myocardial contractility and conductance may result in hypotension, bradycardia and heart failure [102][103][104][105][106]. Older patients in particular, in whom heart failure, sinus node disease and impairment of the cardiac conduction system are more common, may be at an increased risk for this type of interaction.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Diltiazem [102][103][104][105][106]124,125] Negative inotropism Impairment of AV-conduction Heart failure AV-block Nifedipine [107] Negative inotropism Heart failure (rare)…”
Section: Renal Eliminationmentioning
confidence: 99%
See 1 more Smart Citation